Hedgehog Signaling in Pancreatic Fibrosis and Cancer. Issue 10 (March 2016) - Bai, Yongyu; Bai, Yongheng; Dong, Jiaojiao; Li, Qiang; Jin, Yuepeng; Chen, Bicheng; Zhou, Mengtao
Abstract : Abstract: The hedgehog signaling pathway was first discovered in the 1980s. It is a stem cell-related pathway that plays a crucial role in embryonic development, tissue regeneration, and organogenesis. Aberrant activation of hedgehog signaling leads to pathological consequences, including a variety of human tumors such as pancreatic cancer. Multiple lines of evidence indicate that blockade of this pathway with several small-molecule inhibitors can inhibit the development of pancreatic neoplasm. In addition, activated hedgehog signaling has been reported to be involved in fibrogenesis in many tissues, including the pancreas. Therefore, new therapeutic targets based on hedgehog signaling have attracted a great deal of attention to alleviate pancreatic diseases. In this review, we briefly discuss the recent advances in hedgehog signaling in pancreatic fibrogenesis and carcinogenesis and highlight new insights on their potential relationship with respect to the development of novel targeted therapies.